Congenital Disorders of Glycosylation in Portugal—Two Decades of Experience - Quelhas, D (2022)
Objective: To describe the clinical, biochemical, and genetic features of both new and previously reported patients with congenital disorders of glycosylation (CDGs) diagnosed in Portugal over the last 20 years. Study design: The cohort includes patients with an unexplained multisystem or single organ involvement, with or without psychomotor disability. Serum sialotransferrin isoforms and, whenever necessary, apolipoprotein CIII isoforms and glycan structures were analyzed. Additional studies included measurement of phosphomannomutase (PMM) activity and analysis of lipid-linked oligosaccharides in fibroblasts. Sanger sequencing and massive parallel sequencing were used to identify causal variants or the affected gene, respectively. Results: Sixty-three individuals were diagnosed covering 14 distinct CDGs; 43 patients diagnosed postnatally revealed a type 1, 14 a type 2, and 2 a normal pattern on serum transferrin isoelectrofocusing. The latter patients were identified by whole exome sequencing. Nine of them presented also a hypoglycosylation pattern on apolipoprotein CIII isoelectrofocusing, pointing to an associated O-glycosylation defect. Most of the patients (62%) are PMM2-CDG and the remaining carry pathogenic variants in ALG1, ATP6AP1, ATP6AP2, ATP6V0A2, CCDC115, COG1, COG4, DPAGT1, MAN1B1, SLC35A2, SRD5A3, RFT1, or PGM1. Conclusions: Portuguese patients with CDGs are presented in this report, some of them showing unique clinical phenotypes. Among the 14 genes mutated in Portuguese individuals, 8 are shared with a previously reported Spanish cohort. However, regarding the mutational spectrum of PMM2-CDG, the most frequent CDG, a striking similarity between the 2 populations was found, as only 1 mutated allele found in the Portuguese group has not been reported in Spain.